Facile One‐Step Synthesis of Black Phosphorus via Microwave Irradiation with Excellent Photocatalytic Activity. (10th September 2018) - He, Dongyang; Zhang, Zhaocheng; Qu, Jiao; Yuan, Xing; Guan, Jiunian
Abstract: A rapid one‐step microwave‐assisted liquid‐phase synthesis (MLS) method of black phosphorus (BP) is reported for the first time in this work. Under microwave irradiation, BP is generated within 45 min. The lattice spaces of the as‐prepared BP are determined as 0.338 and 0.158 nm, belonging to the (021) and (220) planes of BP, respectively. BP is grown in situ on red phosphorus (RP), which can be used directly as a metal‐free photocatalyst. The coupled BP–RP heterostructure exhibits an excellent performance in visible‐light photocatalytic degradation of methylene blue with BP acting as cocatalyst. The enhanced photocatalytic activity of BP–RP heterostructure compared with RP itself is obtained and explained in terms of the efficient separation of photogenerated electrons (eCB − ) and holes (h + ) due to the well‐matched energy level of BP and RP. The new‐developed MLS method holds great promise for developing an easy and efficient preparation method of BP for photocatalytic applications. Abstract : A facile microwave‐assisted liquid‐phase synthesis method of black phosphorus (BP) is reported for the first time. Under microwave irradiation, BP is generated within 45 min. BP is grown in situ on red phosphorus (RP), which can be used directly as a metal‐free photocatalyst. The BP–RP heterostructure exhibits excellent performance in visible‐light photocatalytic degradation of methylene blue.